(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1989)
This study was done with the purpose of obtaining information on the cutting height for maximum yield of Elephant grass (Pennisetum purpureum, Schumach). The experimental design consisted of a randomized block with three main treatments (cutting heights) and four replications. Plots were harvested four times at 45 - day intervals (split plot on time). The results obtained and the interpretation of the statistical analysis led to the following conclusion: the cutting height, at 10 cm above ground level, yielded the highest forage quantity.